2012
DOI: 10.5194/nhess-12-1811-2012
|View full text |Cite
|
Sign up to set email alerts
|

Urban vulnerability and resilience within the context of climate change

Abstract: Abstract. Natural hazards, due to climate change, are particularly damaging in urban areas because of interdependencies of their networks. So, urban resilience has to face up to climate risks. The most impacting phenomenon is the urban heat island (UHI) effect. The storage capacity of heat is depending on shapes of buildings, public spaces, spatial organization, transport or even industrial activities. So, adaptive strategies for improving urban climate could be possible in different ways. In the framework of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The term secondary data are used in this study to refer to data that are examined to respond to research questions that are different from the ones the original collector sought to answer (Vartanian 2011). The secondary data sources were based on recent studies that address urban resilience at the global level, particularly Africa (Leichenko 2011;Storch et al 2011;López-Marrero and Tschakert 2011;Tromeur et al 2012;Pearson et al 2014;Rafael et al 2015;Cobbinah and Poku-Boansi 2018;Darkwah et al 2018;Poku-Boansi and Cobbinah 2018).…”
Section: Data Sources and Collection Methodsmentioning
confidence: 99%
“…The term secondary data are used in this study to refer to data that are examined to respond to research questions that are different from the ones the original collector sought to answer (Vartanian 2011). The secondary data sources were based on recent studies that address urban resilience at the global level, particularly Africa (Leichenko 2011;Storch et al 2011;López-Marrero and Tschakert 2011;Tromeur et al 2012;Pearson et al 2014;Rafael et al 2015;Cobbinah and Poku-Boansi 2018;Darkwah et al 2018;Poku-Boansi and Cobbinah 2018).…”
Section: Data Sources and Collection Methodsmentioning
confidence: 99%
“…Again, Adachi et al [92] revealed the present and potential increased urban heat island (UHI) in Tokyo, Japan, and called for increased mitigation measures against UHI for the city. Additionally, Tromeur et al [93] described the energy needs for residential buildings and comfort (heat) in 10 French cities and indicated their susceptibility. For improved mitigation, Tromeur et al [93] suggested the need for city managers to think about green space spots, push polluting actions beyond the city, and lower car traffic for riders.…”
Section: Extreme Temperaturesmentioning
confidence: 99%
“…Additionally, Tromeur et al [93] described the energy needs for residential buildings and comfort (heat) in 10 French cities and indicated their susceptibility. For improved mitigation, Tromeur et al [93] suggested the need for city managers to think about green space spots, push polluting actions beyond the city, and lower car traffic for riders. McPhee et al [94] informed us about the potential heat events in Santiago, Chile, due to increasing temperatures and decreasing precipitation and recommended the need for effective adaptation plans.…”
Section: Extreme Temperaturesmentioning
confidence: 99%
“…First and foremost, we name that hazards that are sensitive to questions linked to climate change (e.g. heat waves) (Tromeur et al, 2012). However, above all, it is the predominance of flood hazards that is discussed in six articles (Mebarki et al, 2012;Gersonius et al, 2012;Toubin et al, 2012;Beraud et al, 2012;Lhomme et al, 2013;Eleutério et al, 2013).…”
Section: Implementing Resilience -Lessons To Be Drawn From This Specimentioning
confidence: 99%